OpenStudy (anonymous):

Marcie solved the following inequality and her work is shown below: −2(x − 5) − 12 ≤ 4 + 6(x + 3) −2x + 10 − 12 ≤ 4 + 6x + 18 −2x − 2 ≤ 6x + 22 −8x ≤ 24 x ≤ −3 What mistake did Marcie make in solving the inequality?

OpenStudy (anonymous):

Distribute so you can eliminate the () \[-2x+10-12\le4+6x+18\] combine like terms and simplify

OpenStudy (anonymous):

So -2 +6x ?

OpenStudy (anonymous):

What mistake did Marcie make in solving the inequality? She subtracted 6x from both sides when she should have added 2x. She added 2 to both sides when she should have subtracted 22. When dividing by −8, she did not change the ≤ to ≥. She did not make a mistake

OpenStudy (anonymous):

If you multiply or divide by a negative number when solving an inequality, you must reverse the sign. This example the last step did not flip the sign. it should have said\[x \ge-3\]

OpenStudy (anonymous):

She made a mistake on the last line

OpenStudy (anonymous):

So the dividing part ?

OpenStudy (anonymous):

yes. When dividing by a negative, you must flip the sign

OpenStudy (anonymous):

oh okay i get it